As interfaces entre linguagens audiovisuais e práticas pedagógicas em História e Geografia: experiências, possibilidades e limites no curta metragem como uma outra compreensão do local e do vivido - Perinelli Neto, Humberto [UNESP]; Paziani, Rodrigo Ribeiro (My University, 2012)
Specifically in the teaching practices of History and Geography notes a concern with the construction of school knowledge based on observance of categories such as 'everyday' and 'place', which emphasize a look intensively focused on the local context of the students - element (res) significance, situated in time and space, the representations and actions of individuals, the (re) defining their identities (individual and / or collective) and rights to citizenship. However, both educators in history, as in geography, should be alert to some limits of a strictly pedagogical 'localist'. When it comes to use of language technology audiovisual in line with the pedagogical existing in “PCN's” history and geography, one must keep in mind that not just resize the movie to local level (whether in the classroom or outside), or elect the 'localism' as the new panacea of a certain 'pedagogy' of audiovisual language. With the desire to promote the development of new methods of teaching history and geography is that we designed a research project. This is creating opportunity with the possibility of graduating videos reflect on the teaching of history and geography, according to the use of a new technological language and art (cinema), the association with the reality of the students (hence the site survey and urban) as well as the promotion of an active and critical dialogue with the PCNs’s recommendations.

Nota-se especificamente nas práticas de ensino de História e Geografia uma preocupação com a construção de saberes escolares baseados na observância de categorias como ‘cotidiano’ e ‘lugar’, que enfatizam um olhar intensivamente voltado para o contexto local dos alunos – elemento de (res)significação, num tempo e espaço situados, das representações e as ações dos sujeitos, da (re)definição de suas identidades (individuais e/ou coletivas) e dos direitos à cidadania. Contudo, tanto os educadores em História, quanto em Geografia, devem ficar alertas para alguns limites de uma proposta pedagógica estritamente ‘localista’. Quando se fala de uma utilização da linguagem tecnológica audiovisual em consonância com as propostas pedagógicas existentes nos PCN’s de História e Geografia, é preciso ter em mente que não basta redimensionar o cinema à esfera local (seja em sala de aula ou fora dela), nem eleger o ‘localismo’ como a nova panacéia de uma certa ‘pedagogia’ da linguagem audiovisual. Com o anseio de promover o desenvolvimento de novas metodologias do ensino de história e de geografia é que foi elaborado um projeto de pesquisa. Trata-se de oportunizar com os vídeos a possibilidade dos graduandos refletirem sobre o ensino de história e de geografia, segundo a utilização de uma nova linguagem tecnológica e artística (o cinema), a associação com a realidade dos alunos (daí o estudo do local e do urbano), bem como a promoção de um diálogo ativo e critico com as recomendações do PCN (1998).
The interfaces between visual languages and educational practices in history and geography: experiences, possibilities and limitations of short film as an other understanding about the local and lived
Keywords: História; Geografia; Cinema; Linguagem tecnológica; Metodologia; History; Geography; Cinema; Technological language; Methodology